2021
DOI: 10.3389/fcell.2021.692160
|View full text |Cite
|
Sign up to set email alerts
|

m6A Modification Mediates Mucosal Immune Microenvironment and Therapeutic Response in Inflammatory Bowel Disease

Abstract: Accumulating evidence links m6A modification with immune infiltration. However, the correlation and mechanism by which m6A modification promotes intestinal immune infiltration in inflammatory bowel disease (IBD) is unknown. Here, genomic information from IBD tissues was integrated to evaluate disease-related m6A modification, and the correlation between the m6A modification pattern and the immune microenvironment in the intestinal mucosa was explored. Next, we identified hub genes from the key modules of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…M6A is a ubiquitous RNA modification that plays a vital role in human tumors ( 27 ). A study showed that M6A-related genes were dysregulated in CRC, and their expression was associated with CRC progression and poor prognosis ( 28 ). Moreover, FTO gene may have a key role in mucosal immune health ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M6A is a ubiquitous RNA modification that plays a vital role in human tumors ( 27 ). A study showed that M6A-related genes were dysregulated in CRC, and their expression was associated with CRC progression and poor prognosis ( 28 ). Moreover, FTO gene may have a key role in mucosal immune health ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FTO gene may have a key role in mucosal immune health ( 27 ). A recent study found that m6A modification may affect immune infiltration and therapeutic response in inflammatory bowel disease (IBD) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…44 More importantly, a recent study by Chen et al emphasized the importance of the m6A modification in regulating the immune infiltration and therapeutic response in inflammatory bowel disease. 45 These findings suggested that m6A modification plays important role in the pathogenesis of intestinal-related diseases. As far as we know, no report has elucidated the role of METTL3-mediated m6A modification in functional constipation.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, increasing studies have reported a role for type I IFNs (interferons) in the pathogenesis of different subsets of RA patients, indicating that IFN-a/bactivity may have essential clinical utility in predicting response to tumor necrosis factor antagonists (35-37). Chen et al also found that the expression of m6A phenotype-related hub genes might predict a therapeutic response to anti-TNF therapy in inflammatory bowel disease (38). Previous studies have demonstrated that m6A involves the progression of the inflammatory response by affecting TNF-a degradation and regulation.…”
Section: Discussionmentioning
confidence: 97%
“…Chen et al. also found that the expression of m6A phenotype-related hub genes might predict a therapeutic response to anti-TNF therapy in inflammatory bowel disease ( 38 ). Previous studies have demonstrated that m6A involves the progression of the inflammatory response by affecting TNF-α degradation and regulation.…”
Section: Discussionmentioning
confidence: 99%